If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w + 29 = 2(w + -3) Reorder the terms: 29 + -5w = 2(w + -3) Reorder the terms: 29 + -5w = 2(-3 + w) 29 + -5w = (-3 * 2 + w * 2) 29 + -5w = (-6 + 2w) Solving 29 + -5w = -6 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. 29 + -5w + -2w = -6 + 2w + -2w Combine like terms: -5w + -2w = -7w 29 + -7w = -6 + 2w + -2w Combine like terms: 2w + -2w = 0 29 + -7w = -6 + 0 29 + -7w = -6 Add '-29' to each side of the equation. 29 + -29 + -7w = -6 + -29 Combine like terms: 29 + -29 = 0 0 + -7w = -6 + -29 -7w = -6 + -29 Combine like terms: -6 + -29 = -35 -7w = -35 Divide each side by '-7'. w = 5 Simplifying w = 5
| 10x^2-6xy+y^2-25=0 | | 10x^2-6xy+y^2=25 | | 6(u+4)=-2u+40 | | -3v+42=-5(v-8) | | 64000=x(1-0.3) | | 26=3y-16 | | 9x+24=2x+3 | | 4cos^2x+3cosx=0 | | 158=67-x | | 16y=0.6y | | -4=y-7 | | -5a-(3a-7)= | | x^2-2x+8=20 | | b(y-b)=d(y-d) | | -5a-3a-7= | | -2+3(-6y-7)=-5(-5y-1)+2 | | 6=3+y | | x^2+3x-7=32 | | x^2+x+10=35 | | x^2+3x+4=16 | | x+10=24-x | | x^2+x-7=3 | | x^2+x-7=14 | | 0=44x^2-88x+74 | | 0=44x^2-88t+74 | | x^3+3=14 | | 24=4m | | -7(2x+3)+11x= | | x^2+2x+1=40 | | G=9/2(p-67) | | x=1-13/5 | | 5x+13y+5=0 |